MANAJEMEN PEMBELAJARAN BTQ MELALUI METODE IQRA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ALQURAN - Aan Sutianah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
Reading the Qur'an for Muslims is a worship of Allah. How to plan, organize, implement, and evaluate the Qur'an Reading (BTQ) learning through the Iqro method 'in an effort to improve the ability to read Alquran at MIN 6 Pangandaran Regency? The aim is to find out and analyze the planning, organizing, implementing, and evaluating learning to read the Qur'an (BTQ) through the Iqro method 'in an effort to improve the ability to read the Qur'an. With descriptive qualitative methods, in an effort to obtain a general picture of matters relating to the management of learning to read and write the Qur'an. The data sources are BTQ teachers and students. Secondary data in the form of information from people and notes; books, reports and other forms. The results of the research show that Iqro learning planning 'is administratively unorganized and not conceptualized. Organizing BTQ learning through the Iqro method 'has not been applied professionally and proportionally. Iqro learning 'in class homogeneously according to each volume. While in the selection of methods applied in learning the Iqro method 'at MIN 6 Pangandaran, they are: individual, classical individual, classical reading refer to, reading, writing, lecturing and reading practice. Evaluations applied in BTQ through the Iqro method 'are in accordance with the Iqro manual' but are not well administered. There is no administrative data on the evaluation results.